Penerapan Metode Mindscaping dalam Pembelajaran Fisika sebagai Upaya Meningkatkan Hasil Belajar Siswa - Erdawaty, Sri; Hikmawati, Hikmawati; Kosim, Kosim (IKIP Mataram, 2018)
[Title: The Implementation of Mindscaping Method in Physics Learning as an Effort to Improve Student Learning Outcomes]. This study aims to improve the activities and outcomes of student physics learning by applying the mindscaping method. This type of research is classroom action research conducted in three cycles. Each cycle consists of planning, action, observation, evaluation and reflection. Student learning activity data is obtained by observation while student learning outcomes data are obtained by giving objective tests at the end of each cycle. The application of the mindscaping method in this study is said to be successful if 85% of students achieve learning outcomes greater or equal to 65, while student learning activities are at least active categories. The results of the study showed an increase in student learning activities each cycle, namely in the first cycle the category was quite active to be very active in the second cycle and in the third cycle. Student learning outcomes can be seen from the classical completeness value which has increased in each cycle, each has a value of 76% in the first cycle, 80% in the second cycle, and 92% in the third cycle. Thus it can be concluded that the application of the mindscaping method has succeeded in increasing the activities and results of student physics learning.